Sinergi Pemerintah dan Sektor Swasta dalam Menerapkan Ekonomi Pancasila di Indonesia: Synergy between the Government and the Private Sector in Implementing Panacasila Economics in Indonesia - Ahmad Muhammad Mustain Nasoha; Sinta Cahya Amelia; Dini Kairiya Hasna; Livia Septiana; Rindu Anggriani (LITERA: Jurnal Ilmiah Mutidisiplin, 2025)
The Pancasila Economy is a uniquely Indonesian economic system based on the values of mutual cooperation, social justice, and shared prosperity. However, in practice, its implementation still faces challenges, such as social inequality and the dominance of market interests. Therefore, synergy between the government and the private sector is crucial for realizing the principles of the Pancasila Economy in practice. This study aims to analyze how cooperation between the government and the private sector can support the implementation of the Pancasila Economy in Indonesia. The method used is a literature review with a qualitative descriptive approach, collecting data from books, journals, economic policies, and public-private partnership practices. The results indicate that synergy can be built through collaborative policies, increasing the role of the private sector in social programs, and government oversight to ensure that economic activities remain oriented towards humanitarian values and justice. In conclusion, the implementation of the Pancasila Economy will be more effective if the government and the private sector work together in a balanced manner, supporting each other in creating equitable and sustainable development.